Novel modulators of blood pressure with age: a physiological and bioinformatics-based approach - Bachman, Nate P., author; Braun, Barry, advisor; LaRocca, Thomas J., advisor; Chicco, Adam J., committee member; Gentile, Christopher L., committee member (Colorado State University. Libraries, 2021)
Systolic blood pressure (SBP) increases with age and is a significant risk factor cardio- and cerebrovascular diseases. While the causes of high blood pressure (hypertension) have been extensively studied, the causes of the age-related rise in blood pressure independent of chronic disease remain unclear. Thus, the identification of novel mechanisms underlying age-related high blood pressure may lead to new strategies to reduce chronic disease risk in older adults. Therefore, the goal of this dissertation was to use both physiological and bioinformatics-based approaches to better elucidate contributors to elevated blood pressure in healthy older adults. The main findings are that 1) inhibition of Rho-kinase (an enzyme that participates in numerous cellular/regulatory pathways) lowers systemic blood pressure in healthy older adults concomitant with reduced vascular resistance but not improved endothelial function, 2) genes expression patterns in peripheral white blood cells differ in healthy older adults with elevated SBP compared to those with normal SBP and transcriptomic (RNA) changes relate to vascular and immune function, and 3) circulating chemokines and whole blood immune-related transcripts track with elevated SBP in healthy older adults. Taken together, this work shows that Rho-kinase, circulating RNA transcripts, and circulating chemokines may be novel therapeutic targets and/or biomarkers of elevated blood pressure in healthy older adults with untreated hypertension.
Keywords: blood pressure; inflammation; transcriptomics; hypertension; aging; Rho-kinase